O lucro do ofensor como critério de quantificação das indenizações por danos morais - FAMPA, Daniel Silva (Universidade Federal do Pará, 2018)
The present study aims to analyze to what extent the offender's profit can be considered a criterion in relation to the quantum of damages fixed by way of moral damages. It adopts the deductive method throughout the investigation, supported by bibliographical research and caselaw survey to confront the hypotheses of the work. In order to answer the problem question, it initially examines the interlocution between the functions of civil liability contemporaneously diffused. It considers compensation to be a dimension of the reparatory function, being essential to adapt this function to the regulations of moral damages, since these are incompatible with the logic of returning to the status quo ante. It contextualizes the reparation of damages in the constitutional system of prime protection to the dignity of human beings, gauging the effects that emanate from the incidence of the ideal of personalization in relations set among individuals. Through a research in the Federal Supreme Court’s virtual database of decisions, it reports the stages of the process of acceptance of moral damages in Brazil, from its unrestricted rejection to its insertion in the Federal Constitution of 1988. In addition, it discusses the most widespread attempts of their conceptualization, accepting, among the proposals that qualify them as a violation of human dignity, the one which is friendlier to the requirement of integral protection of individuals, since this expands the range of possibilities of legal goods that are compensated in case of violation. It acknowledges that the need for compensation for such damages represented the effective entrance door for "new" functions of civil liability in Brazil, since the equitable arbitration, as a model of quantification, grants the judges greater freedom, regarding to the stipulation of the quantum of damages, allowing them to consider criteria that cannot be considered reparatory. First, it examines the problem of quantification from the comparison between the ‘law pricing’ and ‘the equitable arbitration by the judge’ models, indicating their respective manifestations in the internal legal system. It investigates the main criteria of quantification adopted by the Brazilian Courts today, including consideration of the biphasic method, absorbed by the Superior Court of Justice in its law-cases. It explores the teleological connections that the offender's profit parameter holds with the civil liability functions, identifying the possibilities of a double dimension of the damage suffered by the victims in these cases. It concludes that the criterion investigated has a clear reparatory purpose in relation to the offender; therefore, it is not necessary to evoke the punitive or preventive function to support its applicability. Without prejudice to the preceding idea, it is possible to consider a punitive or dissuasive approach in cases of malice or gross fault by the offender, and it is essential that the judges observe, in stipulating the quantum of damages, the nature of the right which was injured, especially considering the extent of right-holders (whether individual or trans individual), which may cause changes in the quantum defined.